Allelopathy and Vegetation in Acacia Tortilis Plantatiuns in Indian Desert - Sundaramoorthy, S; Kalra, Anju (Annals of Arid Zone, 2016)
The properties of soil beneath Acacia tortilis and Prosopis cineraria at Jodhpur did not differ significantly. The common understorey plants of A. tortilis showed lower phytomass and higher phosphorus, potassium, and also nitro n in Ecerhavia difw and Gisekia pfnmlcioides than p. cinerari; J indicating that no apparent competition exists. In A. tortilis, soil extracts exhibited inhibitory effect on germination and seedling growth on pearlmillet, sesame and clusterbean. Leaves + stem leachate showed maximum inhibitory effect. Extracts exhibited higher inhibitory effect than the respective leachate. Concentrations of extracts and leachates were negatively correlated with germination and seedling growth. Sesame was most affected.